(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
The idea of Prompter, drawn from the traditional figure who whispers the text, was approached as a conceptual operator that reorganizes temporalities and co‑agency, expanding reenactment as a procedure that operates in the friction between archive and gesture. The study relied punctually on Schneider’s notions of return and persistence, Carlson’s concept of theatrical memory, and Derrida’s notion of the trace to analyze the performances Apokalypse, Ficções, Sopro, and the practices of the Wooster Group and Gob Squad. Regimes of operation of the Prompt, scenic bodies, and modes of mediation were identified. The process revealed an interstitial presence shaped by the gap between archive and action.